CYSTIC ECHINOCOCCOSIS AS A PUBLIC HEALTH PROBLEM IN LATIN AMERICA AND NEW APPROACHES TO ITS CONTROL - Ferreira, Ciro (2007)
Cystic echinococcosis is a zoonosis caused by a cestode, Echinococcus granulosus, of the Taeniidae family. The adult form of the tapeworm affects canids, particularly dogs and foxes, while the larva is harbored by sheep, cattle, goats and other mammals.